2009
DOI: 10.1111/j.1365-3040.2009.01939.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical microtubule as a sensor and target of nitric oxide signal during the defence responses to Verticillium dahliae toxins in Arabidopsis

Abstract: The molecular mechanisms of signal transduction of plants in response to Verticillium dahliae (VD) are not known. Here, we show that Arabidopsis reacts to VD-toxins with a rapid burst of nitric oxide (NO) and cortical microtubule destabilization. VD-toxins treatment triggered a disruption of cortical microtubules network. This disruption can be influenced by NO production. However, cortical microtubule disruptions were not involved in regulating the NO production. The results indicated that NO may act as an up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 67 publications
0
36
0
Order By: Relevance
“…18,19 Taken together, these data suggest that NO serves as a signaling intermediate downstream of H 2 O 2 to modulates the dynamic microtubule cytoskeleton during the responses to VD-toxins in Arabidopsis.…”
Section: No and H 2 O 2 Modulates Vd-toxins-induced Dynamic Microtubumentioning
confidence: 89%
See 1 more Smart Citation
“…18,19 Taken together, these data suggest that NO serves as a signaling intermediate downstream of H 2 O 2 to modulates the dynamic microtubule cytoskeleton during the responses to VD-toxins in Arabidopsis.…”
Section: No and H 2 O 2 Modulates Vd-toxins-induced Dynamic Microtubumentioning
confidence: 89%
“…[13][14][15][16][17] We have recently demonstrated that NO and H 2 O 2 can act as an upstream signaling molecule to modulate the dynamic microtubule cytoskeleton during the defense responses to Verticillium dahliae (VD) toxins in Arabidopsis. 18 To investigate the interaction between the NO and H 2 O 2 production, wild-type seedlings were co-treated with VD-toxins plus DPI (a potent inhibitor of NADPH oxidase), DMTU (a H 2 O 2 scavenger), cPTIO (a NO scavenger) and sodium tungstate (a potent inhibitor of nitrate reductase).…”
mentioning
confidence: 99%
“…In the previous studies, we showed that MTs play an important role in the signaling pathway for mediating the defense response against Vd toxins in Arabidopsis (Shi et al, 2009;Yao et al, 2011). Therefore, we explored whether H2Bub and the dynamics of MTs are connected during the defense response to Vd toxins.…”
Section: H2bub Is Involved In Modulating the Dynamics Of Mts Induced mentioning
confidence: 98%
“…Reduced MT dynamics have also been demonstrated to render plants less susceptible to Tobacco mosaic virus (Ouko et al, 2010). We have previously demonstrated that MTs play an important role in the defense response against Verticillium dahliae (Vd) toxins in Arabidopsis (Shi et al, 2009;Yao et al, 2011). However, the precise mechanisms regulating the dynamics and organization of the MTs remain poorly understood.…”
Section: Monoubiquitination1 [Hub1] and Hub2) And Three E2 Conjugasesmentioning
confidence: 99%
See 1 more Smart Citation